Labor market effects of unemployment insurance design - Tatsiramos, Konstantinos; Van Ours, Jan (Wiley, 2014)
With the emergence of the Great Recession unemployment insurance (UI) is once again at the heart of the policy debate. In this paper, we focus on the recent theoretical and empirical evidence on the labor market effects of UI design. We provide an overview of the design of UI in various countries and we discuss policy issues related to the structure of the UI system, including the pros and cons of a UI system in which the generosity of UI benefits is varying over the business cycle. Finally, we identify potential areas of future research on UI design.